MENINGKATKAN KINERJA GURU DI SMP NEGERI 1 RONGGURNIHUTA MELALUI SUPERVISI AKADEMIK KEPALA SEKOLAH - Tiarma Lasmaria Manurung; Ulung Napitu; Anggiat Sinurat (Prodi Pendidikan Guru Sekolah Dasar (PGSD) FKIP Universitas Pattimura, 2023)
Increasing the quantity of a school is evidence of increasing public trust in the school. Increased public trust does not just come, but is the result of the hard work and performance of the entire school community in producing outstanding students. For this reason, the purpose of this study was to describe the relationship between the academic supervision of school principals and teacher performance. The method used in this research is a qualitative research which aims to obtain an overview of the variables studied. This research was conducted at Ronggurnihuta Public Middle School 1, Pematangsiantar with a total of 21 teachers. To collect data on academic supervision and teacher performance, researchers will use data collection techniques in the form of a Likert scale questionnaire (five levels) and interviews. The data obtained were then analyzed using data reduction techniques and data interpretation. The results of the questionnaire research showed that the teacher's performance at Ronggurnihuta Public Middle School 1 was included in the good category with a score of 4.014 after carrying out continuous academic supervision coordinated by the school principal. This shows that to improve teacher performance, the supervisory role of the school principal is very important. Keywords: teacher performance, academic supervision, academic evaluation